Time to Train: The Involvement of the Molecular Clock in Exercise Adaptation of Skeletal Muscle - Mansingh, Shivani; Handschin, Christoph (Frontiers in Physiology, 2022)
Circadian rhythms regulate a host of physiological processes in a time-dependent manner to maintain homeostasis in response to various environmental stimuli like day and night cycles, food intake, and physical activity. Disruptions in circadian rhythms due to genetic mutations, shift work, exposure to artificial light sources, aberrant eating habits, and abnormal sleep cycles can have dire consequences for health. Importantly, exercise training efficiently ameliorates many of these adverse effects and the role of skeletal muscle in mediating the benefits of exercise is a topic of great interest. However, the molecular and physiological interactions between the clock, skeletal muscle function and exercise are poorly understood, and are most likely a combination of molecular clock components directly acting in muscle as well as in concordance with other peripheral metabolic organ systems like the liver. This review aims to consolidate existing experimental evidence on the involvement of molecular clock factors in exercise adaptation of skeletal muscle and to highlight the existing gaps in knowledge that need to be investigated to develop therapeutic avenues for diseases that are associated with these systems.